2020
DOI: 10.1038/s41598-020-67606-1
|View full text |Cite
|
Sign up to set email alerts
|

Co-evaporation as an optimal technique towards compact methylammonium bismuth iodide layers

Abstract: the most studied perovskite-based solar cells reported up to date contain the toxic lead in its composition. photovoltaic research and development towards non-toxic, lead-free perovskite solar cells are critical to finding alternatives to reduce human health concerns associated with them. Bismuth-based perovskite variants, especially in the form of methylammonium bismuth iodide (MBi), is a good candidate for the non-toxic light absorber. However, the reported perovskite variant MBI thin films prepared by the s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Cross-sectional SEM images, as shown in Figure S12, showed a thick perovskite capping layer, however, the device efficiency was significantly reduced. Recently, Momblona et al reported on similar observations in co-evaporated highly uniform MA 3 Bi 2 I 9 thin films, in which a very low PCE of 0.01% was achieved with a thick capping layer [26]. A thick layer of perovskite regardless of uniformity is probably detrimental for efficient charge transport, because of the high exciton binding energies (up to 300 meV [24]) and exciton gap states (see excitonic absorption peaks in Fig.…”
Section: Double-cation Based Bismuth Iodide Perovskitementioning
confidence: 74%
See 1 more Smart Citation
“…Cross-sectional SEM images, as shown in Figure S12, showed a thick perovskite capping layer, however, the device efficiency was significantly reduced. Recently, Momblona et al reported on similar observations in co-evaporated highly uniform MA 3 Bi 2 I 9 thin films, in which a very low PCE of 0.01% was achieved with a thick capping layer [26]. A thick layer of perovskite regardless of uniformity is probably detrimental for efficient charge transport, because of the high exciton binding energies (up to 300 meV [24]) and exciton gap states (see excitonic absorption peaks in Fig.…”
Section: Double-cation Based Bismuth Iodide Perovskitementioning
confidence: 74%
“…In 2015, Park et al reported Cs 3 Bi 2 I 9 and MA 3 Bi 2 I 9 based mesoscopic heterojunction solar cells yielding power conversion efficiency (PCE) of 1.09% for the former and 0.2% for the latter [24]. Subsequently, efforts have been made to further improve the efficiency by employing suitable electron transport layers [25], vapour deposition [26], solvent engineering [27]; however, the efficiency has been limited. Nevertheless, various solution-based and vaporassisted methods were reported with different solvents [27,28] and fabrication processes leading to PCEs between 0.01% [29] and 1.64% [30].…”
Section: Invited Papermentioning
confidence: 99%
“…To overcome the film morphology limitations reported in the literature on lead‐free bismuth‐based PIMs grown through vapor‐based strategies, [ 25–32 ] in this study we investigated the deposition of MBI using a modified source delivery CVD system. In CVD, the precursors are brought into the vapor phase by heating and are then carried by an inert gas stream to the vicinity of a heated substrate.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that the 2T‐CVD MBI films exhibited a morphology that is considerably improved compared to the prior literature, which typically reported MBI films with noncompact surface morphologies, disconnected/isolated grains, and a large number of pinholes. [ 15–20,25–32 ] The enhancement in surface morphology of 2T‐CVD MBI films compared to the 1T‐counterparts can be attributed to the efficient delivery of the precursors to the substrate region, as enabled by the separate delivery system used for the two precursors, which would lead to the formation of a laminar flow regime (Figure S2, Supporting Information). Consequently, a homogenous reaction of the precursors would occur at or in the immediate vicinity of the substrate surface, as reflected by the high quality of the resultant MBI films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation